Exploring “Everyday Experience Methods” as a means to assess the (social-)psychological comfort of clothing - Matté, L. L. (2018)
One of the main challenges for the Science of Clothing Comfort, is to uncover the intricacies and complexities of the psychological aspects of the clothing comfort perception. The concept and the parameters of this comfort dimension are still in the process of maturing, and the methods and tools to assess this component are still underdeveloped. One of the main drawbacks of the research on the psychological comfort of clothing resides in the dependency of the context and situational information, to elaborate a psychological comfort or discomfort perception. In the realm of the psychological or social-psychological comfort, it’s primordial that the context variables are considered. This pilot study aims at examining the feasibility of assessing the perception of (social-)psychological comfort of clothing, using an everyday experience method. For this purpose, the PACO application (pacoapp.com) was the chosen platform.